OBSESSIVE COMPULSIVE DISORDER AND DISSOCIATION - COMPARISON WITH HEALTHY CONTROLS - Prasko, Jan; Raszka, Michal; Diveky, Tomas; Grambal, Ales; Kamaradova, Dana; Koprivova, Jana; Latalova, Klara; Pastucha, Petr; Sigmundova, Zuzana (Biomedical papers, 2010)
The aim of our study is to examine if the dissociation can influence the intensity of psychopathology in patients suffering from obsessive compulsive disorder and to compare the levels of dissociation in the groups of the patients and healthy subjects.Method: Fifty five patients suffering from obsessive compulsive disorder and 123 healthy controls were included into the study. The patients were psychiatrically assessed. The diagnosis was made using ICD-10 research criteria confirmed with structured interview MINI. The subjective intensity of anxiety and depressive symptoms was evaluated using Beck Anxiety Inventory and Beck Depression Inventory. The intensity of obsessions and compulsions was evaluated using Yale Brown Obsessive Compulsive Scale. All participants were assessed with the Dissociative Experiences Scale (DES).Results: Level of the psychological dissociation assessed with the DES was correlated with the severity of subjective anxiety (p<0.0001), depression (p<0.0001), and with the severity of obsessive-compulsive symptoms (p<0.005). Patients have significantly lower mean score on the DES than healthy controls (p<0.0001).Conclusion: Our results suggest that the level of psychological dissociation in OCD patients is lower than in healthy controls, and is associated with the severity of anxiety, depression and obsessive compulsive symptoms.
Keywords: Obsessive/Compulsive/Disorder/Dissociation/Anxiety/Depression